2008
DOI: 10.1017/s1092852900016436
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Body Dysmorphic Disorder in the United States Adult Population

Abstract: Objective:In clinical samples, body dysmorphic disorder (BDD) is associated with substantial suffering and reduced quality of life. Limited surveys report widely varying prevalence estimates. To better establish the prevalence of BDD, we conducted a United States nationwide prevalence survey.Method:We conducted a random sample national household telephone survey in the spring and summer of 2004 and interviewed 2,513 adults, of whom 2,048 qualified for the BDD-module administration. The computer-assisted, struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
188
4
28

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(257 citation statements)
references
References 26 publications
24
188
4
28
Order By: Relevance
“…To fulfill the diagnostic criteria, they must also experience clinically significant distress or impairment in social, occupational, or other important areas of functioning (American Psychiatric Association, 2013). The prevalence of BDD is reported to be up to 2.4% in the US population (Koran, Abujaoude, Large, & Serpe, 2008). BDD is a chronic condition, which usually develops during adolescence and has significant negative impact on quality of life (Phillips, 2000).…”
Section: Accepted M Manuscript Imagmentioning
confidence: 99%
“…To fulfill the diagnostic criteria, they must also experience clinically significant distress or impairment in social, occupational, or other important areas of functioning (American Psychiatric Association, 2013). The prevalence of BDD is reported to be up to 2.4% in the US population (Koran, Abujaoude, Large, & Serpe, 2008). BDD is a chronic condition, which usually develops during adolescence and has significant negative impact on quality of life (Phillips, 2000).…”
Section: Accepted M Manuscript Imagmentioning
confidence: 99%
“…BDD is relatively common, with prevalence estimates ranging between 1 -2% in the general population (Rief et al, 2006;Koran et al, 2008;Buhlmann et al, 2010). The symptoms of BDD have been associated with substantial psychiatric comorbidity (Gunstad and Phillips, 2003;Pavan et al, 2008), poor quality of life (Didie et al, 2007) and alarmingly high suicide rates (Phillips et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…As the prevalence of BDD was higher in the interview sample compared to the total sample, at least part of the explanation is probably that women with BDD are more likely to be single. Previous large population studies have reported that individuals with BDD are more frequently divorced or single than individuals without BDD (Rief et al, 2006;Koran et al, 2008). This is not surprising, since the disorder often leads to impaired functioning in relationships, socializing and intimacy (Phillips, 1991).…”
Section: Discussionmentioning
confidence: 97%
“…BDD appears to be relatively common. The three largest studies (n>2000) in general populations found BDD prevalence rates of 1.7-2.4% (Rief et al, 2006;Koran et al, 2008;Buhlmann et al, 2010). Using structured clinical interviews examining community samples, prevalence rates of 0.7-3% have been reported (Faravelli et al, 1997;Bienvenu et al, 2000;Otto et al, 2001).…”
Section: Introductionmentioning
confidence: 99%